2010
DOI: 10.1111/j.1460-9568.2010.07216.x
|View full text |Cite
|
Sign up to set email alerts
|

Protein kinase Cγ is a signaling molecule required for the developmental speeding of α‐amino‐3‐hydroxyl‐5‐methyl‐4‐isoxazole‐propionate receptor kinetics

Abstract: A key step in the maturation of glutamate synapses is the developmental speeding of alpha-amino-3-hydroxyl-5-methyl-4-isoxazole-propionate receptor (AMPA-R) kinetics, which occurs via a switch in receptor subtypes. However, the molecular components required for the switch in receptors are unknown. Here, we used the zebrafish preparation to show that activation of protein kinase C (PKC)gamma is necessary for the developmental speeding of AMPA-R kinetics. Targeted knockdown of PKCgamma with an antisense morpholi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…Initial studies on PRKCG indicated deficits in spatial and contectual learning, likely due to abnormal hippocampal LTP induction in mutant PRKCG mice [87,88]. Others have shown that PKC gamma traffics AMPARs in zebrafish in an NSF and PICK1 dependent manner, resulting in miniEPSC potentiation [89][90][91]. Additionally, NSF attachment protein beta (NAPB or β-SNAP) can regulate NSF and PICK1 mediated AMPAR trafficking, where βSNAP directly binds to PICK1 and allows NSF to dissasemble PICK1-AMPAR complexes [92].…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies on PRKCG indicated deficits in spatial and contectual learning, likely due to abnormal hippocampal LTP induction in mutant PRKCG mice [87,88]. Others have shown that PKC gamma traffics AMPARs in zebrafish in an NSF and PICK1 dependent manner, resulting in miniEPSC potentiation [89][90][91]. Additionally, NSF attachment protein beta (NAPB or β-SNAP) can regulate NSF and PICK1 mediated AMPAR trafficking, where βSNAP directly binds to PICK1 and allows NSF to dissasemble PICK1-AMPAR complexes [92].…”
Section: Discussionmentioning
confidence: 99%
“…Zebrafish Mauthner cells express AMPA receptors from as early as 28-32 hpf (Ali et al, 2000). Similar to mammalian systems, the kinetic properties of AMPAR currents speed up during development (Patten and Ali, 2007;Patten et al, 2010), due in part to a switch in subunits and an increase in the expression of GluA2-containing receptors. Activation of PKCc appears to play a role in this developmental change as knockdown of PKCc prevents both the subunit switch and the speeding up of receptor kinetics (Patten and Ali, 2009;Patten et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Similar to mammalian systems, the kinetic properties of AMPAR currents speed up during development (Patten and Ali, 2007;Patten et al, 2010), due in part to a switch in subunits and an increase in the expression of GluA2-containing receptors. Activation of PKCc appears to play a role in this developmental change as knockdown of PKCc prevents both the subunit switch and the speeding up of receptor kinetics (Patten and Ali, 2009;Patten et al, 2010). Because TARP expression is correlated with a speeding up of AMPAR kinetics, we asked whether zebrafish express the prototypical TARP, stargazin (Cacng2), and if it played a role in the development of AMPAR-containing synapses.…”
Section: Introductionmentioning
confidence: 99%
“…Embryonic development is very rapid; the fertilized eggs hatch in 2 days, and the embryos are transparent, allowing extensive imaging studies to be performed on whole organisms. The genome has been sequenced and the technology is available to either knockdown or knockout proteins of interest (Ekker, ; Nasevicius and Ekker, ; Patten et al, ; Tallafuss et al, ). Moreover, one can closely examine escape responses and swimming behaviors.…”
Section: Introductionmentioning
confidence: 99%